Ancient dog introgression into the Iberian wolf genome may have facilitated adaptation to human-dominated landscapes - Lobo, Diana; Morales, Hernán E.; Van Oosterhout, Cock; López-Bao, José Vicente; Silva, Pedro; Llaneza, Luis; Pacheco, Carolina; Castro, Diana; Hernández-Alonso, Germán; Pacheco, George; Archer, John; Gilbert, M. Thomas P.; et al.

(untitled) (Genome Research, 2025)
Understanding how large carnivores respond to increasingly human-dominated landscapes will determine their future adaptive potential. The Iberian wolf (Canis lupus signatus), a gray wolf subspecies endemic to the Iberian Peninsula (Portugal and Spain), has uniquely persisted in human-dominated landscapes, unlike many other wolf populations that faced widespread extinction across Europe during the twentieth century. In this study, we conducted a comprehensive genome-wide analysis of 145 historical and contemporary Iberian wolf samples to investigate whether hybridization with domestic dogs resulted in genetic introgression. We identified a dog-derived block on Chromosome 2 in Iberian wolves, displaying signatures consistent with introgression and high nucleotide similarity among introgressed individuals. Additionally, our estimates place the average timing of introgression between 6100 and 3000 years ago, with low sequence divergence to dogs from the Iberian Peninsula suggesting a single local origin for the hybridization event. Using forward genetic simulations, we show that the introgressed haplotype is most likely being maintained in Iberian wolves by selection. The introgressed dog variants are located within the MAST4 gene, which has been linked to neurological disorders, including cognitive and motor developmental delays, hinting at a potential role in cognitive behavior in Iberian wolves. This study uncovers a case of putative adaptive introgression from domestic dogs into wolves, offering new insights into wild canids’ adaptation to human-dominated landscapes.